Antimicrobial resistance and genotyping of Mycobacterium leprae in Venezuela - Sisco, Maria Carolina; Brum Fontes, Amanda N.; Lessmann, Lucibel Crespo; Rada, Elsa; Prado Palacios, Yrneh Y.; Vasconcellos, Sidra E. G.; de Waard, Jacobus H.; Suffys, Philip N. (Frontiers in Tropical Diseases, 2023)
Leprosy is a neglected tropical disease that leads to physical disability and social discrimination. The active surveillance of new cases and vigilance for drug resistance can decrease the incidence, and improve the clinical outcomes of people affected by it. We analyzed, with molecular biology techniques, a set of skin biopsy samples from 25 Venezuelan patients. The patients had been diagnosed with leprosy in 2014 and early 2015, and 15 were relapse cases. The samples were tested for molecular drug resistance to dapsone, rifampicin, and fluoroquinolones. In addition, we performed molecular epidemiology analysis through multiple-locus variable-number tandem repeat analysis (MLVA) and single nucleotide polymorphism (SNP) typing. We did not find evidence of drug resistance and 76% of the samples (n = 16) had isolates belonging to SNP type 3. Genotype profiles allowed us to rule out the possibility of re-infection in a patient with persistent symptoms after treatment, as well as that of household transmission in two more patients. Although our sampling is relatively small, very similar or even identical Mycobacterium leprae genotypes were observed in Miranda State. The presence of this cluster is highly suggestive of high rates of local transmission and, in turn, the need to better control this disease. Finally, the copy number distribution of minisatellite 18–8 in a considerable number of SNP type 3 strains strongly suggests the presence of a sublineage of this disease that is particular to Venezuela.